2018
DOI: 10.1177/0748233718773182
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plasma concentrations of organochlorine pesticides and polychlorinated biphenyls in pet cats and dogs

Abstract: The aim of this study was the determination of plasma concentrations of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) in cats and dogs and evaluation of their prevalence and possible effects. The concentrations of nine OCPs, such as α-hexachlorocyclohexane (HCH), β-HCH, γ-HCH, hexachlorobenzene (HCB), aldrin, 2,4'-dichlorodiphenyltrichloroethane (2,4'-DDT), 4,4'-DDT, 2,4'-dichlorodiphenyldichloroethylene (2,4'-DDE) and 4,4'-DDE and 16 PCBs (PCB-28, -52, -70, -74, -81, -99, -101, -118, -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
3
1
1
Order By: Relevance
“…In the case of gender, there was no difference between females and males, except total OCPs and total PAHs. This result was similar to that reported in our previous study performed on cats and dogs (Yavuz et al., 2018).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the case of gender, there was no difference between females and males, except total OCPs and total PAHs. This result was similar to that reported in our previous study performed on cats and dogs (Yavuz et al., 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, all PCBs were detected in dog plasma samples (0.52–6.62 ng/g lipid), and 10 of 16 PCBs were detected in cats (0.58–5.66 ng/g lipid). These results were similar to those reported in previous studies performed on cats and dogs in different countries, such as Pakistan, France, UK, Spain and Japan (Yavuz et al., 2018). Iatrou et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to other results in which levels of organochlorine pesticides in plasma (OCP) were higher in cats, the results of the study conducted by Yavuz et al [198] in 15 cats and 21 dogs revealed much higher levels of OCP (α-hexachlorocyclohexane (HCH), β-HCH, γ-HCH, hexachlorobenzene (HCB), aldrin, 2,4 -dichlorodiphenyltrichloroethane (2,4 -DDT), 4,4 -DDT, 2,4 -dichlorodiphenyldichloroethylene (2,4 -DDE), and 4,4 -DDE among canine companions.…”
Section: Pets As Sentinels and Models In Comparative Human-pet Oncolo...contrasting
confidence: 70%
“…Hexachlorobenzene is a long-lived organochlorine compound the benzene ring of which is a closed conjugated system (Yavuz et al, 2018), making chlorine difficult to replace. The more substituted chlorine is, the greater its toxicity and resistance to degradation will be.…”
Section: Discussionmentioning
confidence: 99%